2007
DOI: 10.1021/jp074853q
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Reaction in cAPK Protein Kinase-Free Energy Quantum Mechanical/Molecular Mechanics Simulations

Abstract: We present results of a theoretical analysis of the phosphorylation reaction in cAMP-dependent protein kinase using a combined quantum mechanical and molecular mechanics (QM/MM) approach. Detailed analysis of the reaction pathway is provided using a novel QM/MM implementation of the nudged elastic band method, finite temperature fluctuations of the protein environment are taken into account using free energy calculations, and an analysis of hydrogen bond interactions is performed on the basis of calculated fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
183
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(206 citation statements)
references
References 58 publications
23
183
0
Order By: Relevance
“…2). These values are similar to those predicted by theoretical calculations for the loose transition state in the S N 2 phosphoryl transfer (46).…”
Section: Discussionsupporting
confidence: 89%
“…2). These values are similar to those predicted by theoretical calculations for the loose transition state in the S N 2 phosphoryl transfer (46).…”
Section: Discussionsupporting
confidence: 89%
“…Experimental and theoretical studies have demonstrated that, in phosphoryl transfer by kinases and polymerases, nucleophilic attack on the target phosphate proceeds through a conformation that resembles a trigonal-bipyramidal transition state (31) and that phosphoryl transfer can occur through either an associative or a dissociative mechanism (31)(32)(33). A conserved aspartate (D813 in EGFR, D166 in protein kinase A) is proposed to function as a base acceptor for proton transfer from the hydroxyl group of the substrate, as depicted by the red arrows in Fig.…”
Section: Quantum Mechanics/molecular Mechanics (Qm/mm) Simulation Ofmentioning
confidence: 99%
“…5) with the subsequent binding of second inhibitory metal ion (13). The binding of the second metal ion promotes its action as a Lewis base that must work on the β-γ bond of the ATP molecule to aid the removal of the terminal γ-PO 4 (31). Efficient binding of the two metal ions at the active site by residues N171 and D184 forms the basis of an efficient phosphotransfer process.…”
Section: Y204a Mutation Abolishes the Synergy Between Nucleotide Andmentioning
confidence: 99%